Efficient targeted mutagenesis in the monarch butterfly using zinc-finger nucleases - Merlin, Christine; Beaver, Lauren E.; Taylor, Orley R.; Wolfe, Scot A.; Reppert, Steven M. (Genome Research, 2013)
The development of reverse-genetic tools in “nonmodel” insect species with distinct biology is critical to establish them as viable model systems. The eastern North American monarch butterfly (Danaus plexippus), whose genome is sequenced, has emerged as a model to study animal clocks, navigational mechanisms, and the genetic basis of long-distance migration. Here, we developed a highly efficient gene-targeting approach in the monarch using zinc-finger nucleases (ZFNs), engineered nucleases that generate mutations at targeted genomic sequences. We focused our ZFN approach on targeting the type 2 vertebrate-like cryptochrome gene of the monarch (designated cry2), which encodes a putative transcriptional repressor of the monarch circadian clockwork. Co-injections of mRNAs encoding ZFNs targeting the second exon of monarch cry2 into “one nucleus” stage embryos led to high-frequency nonhomologous end-joining-mediated, mutagenic lesions in the germline (up to 50%). Heritable ZFN-induced lesions in two independent lines produced truncated, nonfunctional CRY2 proteins, resulting in the in vivo disruption of circadian behavior and the molecular clock mechanism. Our work genetically defines CRY2 as an essential transcriptional repressor of the monarch circadian clock and provides a proof of concept for the use of ZFNs for manipulating genes in the monarch butterfly genome. Importantly, this approach could be used in other lepidopterans and “nonmodel” insects, thus opening new avenues to decipher the molecular underpinnings of a variety of biological processes.